Evaluation of the red seaweed Mazzaella japonica as a feed additive for beef cattle - Terry, Stephanie A.; Coates, Trevor; Gruninger, Robert; Abbott, D. Wade; Beauchemin, Karen A. (Frontiers in Animal Science, 2023)
Supplementing ruminant diets with macroalgae is gaining interest globally because bromoform-containing seaweeds (e.g., Asparagopsis sp.) have been shown to be highly effective enteric methane (CH4) inhibitors. Some alternative seaweeds decrease in vitro CH4 production, but few have been evaluated in animals. This study examined the effect of including the red seaweed Mazzaella japonica in the diet of beef cattle on dry matter intake (DMI), rumen fermentation, digestibility, nitrogen (N) utilization, and enteric CH4 production. Six ruminally cannulated, mature beef heifers (824 ± 47.1 kg) were used in a double 3 × 3 Latin Square with 35-d periods. The basal diet consisted of 52% barley silage, 44% barley straw and 4% vitamin and mineral supplement (dry matter (DM) basis). The treatments were (DM basis): 0 (control), 1%, and 2% M. japonica. The DMI increased quadratically (P=0.025) with inclusion of M. japonica. Apparent total-tract digestibility of DM decreased linearly (P=0.002) with inclusion of M. japonica, but there were no treatment differences in the digestibility of organic matter, crude protein (CP), neutral detergent fiber, or starch. M. japonica level linearly (P<0.001) increased the N intake of the heifers. Fecal N excretion linearly increased (P=0.020) with M. japonica, but there were no differences in total urinary N excretion, N fractions (allantoin, uric acid), total purine derivatives, microbial purine derivatives absorbed, microbial N flow, or retained N. There were no treatment effects on rumen pH or total VFA; however, adding M. japonica to the diet quadratically (P=0.023) decreased the proportion of acetate. Methane production (g/day) was quadratically (P=0.037) decreased such that the heifers receiving 2% M. japonica produced 9.4% less CH4 than control animals; however, CH4 yield (g/kg DMI) did not differ among treatments. We conclude that supplementing a forage-based diet with up to 2% M. japonica failed to lower enteric CH4 yield of beef heifers. M. japonica can be used in diets to help meet the CP requirements of cattle, but inclusion rate may be limited by high inorganic matter proportion. When comprising up to 2% of the diet, M. japonica cannot be recommended as a CH4 inhibitor for beef cattle diets.